Tonga : 2011 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Alternate Executive Director for Tonga. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Tonga's economy showed recovery from recent shocks on the back of stronger tourism activity and fiscal expansion. In spite of generous grant inflows, Tonga remains at 'high risk of debt distress' according to World Bank-IMF debt sustainability analysis. Executive Directors stressed that fiscal consolidation is necessary to ensure fiscal sustainability, and encouraged authorities to set up a comprehensive debt-management strategy to limit the credit and currency risks. Directors welcomed the government's policy to pursue structural reforms to promote private sector activity and restore fiscal sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet